Evidence-based Guidelines for the Management of Abnormally Invasive Placenta: Recommendations From the International Society for Abnormally Invasive Placenta. Issue 1 (March 2020) - Collins, S.L.; Alemdar, B.; van Beekhuizen, H.J.; Bertholdt, C.; Braun, T.; Calda, P.; Delorme, P.; Duvekot, J.J.; Gronbeck, L.; Kayem, G.; Langhoff-Roos, J.; Marcellin, L.; et al.
Abstract : ( Am J Obstet Gynecol . 2019;220(6):511–526) Abnormally invasive placenta (AIP), or placenta accreta spectrum disorder has been shown to be on the rise worldwide, likely due to increasing cesarean delivery rates. In cases of AIP, the placenta does not separate during delivery and cannot be removed without abnormal bleeding, which can be life-threatening. Management of AIP requires accurate diagnosis and a robust strategy. However, AIP cases are still relatively rare and constructing an optimal management strategy is therefore challenging. While there have been many studies varying in approach to AIP management, most have been small. In this paper, the International Society for Abnormal Invasive Placenta (IS-AIP) aimed to provide evidence-based recommendations for intrapartum management of AIP.